The effect of prolonged floods on Eichhornia crassipes growth in Paraná river floodplain lakes - Neiff, Juan Jose (2001)
The growth response of Eichhornia crassipes was studied in two floodplain lakes with different inundation regimes and one artificial pond isolated from the Paraná River. We measured the number and the length of green leaves for 12 months to obtain leaf density, maximum leaf length and monthly size distribution frequency. We also measured the increase in leaf dry weigth for 21 days at the end of the growing season (March, 1998). In the same occasion and at the end of prolonged floods (August, 1998), water samples and green leaves subsamples were analysed to determine nutrient content. In the last years, the floodplain lakes were frequently affected by extreme floods due to El Niño events.The prolonged inundation condition in the lake that had a long lasting inundation phase (371 days) was characterized by increases in the mean maximum leaf size (up to 111 cm), increases in the modal leaf length (most prominent mode = 105 cm), high increase in biomass (25 g m-2 day-1) and high nutrient content of green leaves (total nitrogen = 2.53%). The growth response was lower in the lake which had less number of flooding days per year (204) than the lake with the longest duration of the flooding. Nevertheless, it was higher than that described in a previous paper for extreme floods of short duration in the same lakes. In the artificial pond, average increase of green leaves biomass accounted to only 5 g m-2 day-1. The total isolation condition was characterized by decreases in the modal leaf length of the mature plants and increases in standing dead leaves density. These results are discussed in the context of the River Pulse Concept and variation on this theme to Paraná River floodplain